Development Of The Game "Pirates Of Nusantara's Sea" Based On The Java Framework As a Medium To Enhance The English Multiliteracy Skills Of 11th-Grade Students at MAN 2 Mojokerto - Rodli, Moh; Yusuf, Yulia Pratitis; Widiastutik, Trisya (International Humanity Advance, Business & Sciences, 2025)
Describing the development, quality, and effectiveness of using the web-based game "Pirates of Nusantara's Sea" as a medium to understand English reading materials is the aim of this research. The techniques developed in this study are based on Multiliteracies and New Literacies from The New London Group, considering the characteristics of Gen Z students, who prefer digital platforms as their learning medium. This research utilized R&D development methods with the ADDIE model, as it aims to produce a viable product for literacy learning media. This is evidenced by an average validation score of 86.29% provided by material and graphic design validators. The findings revealed that the average post-test score of students in the experimental class was 82.6, compared to 68.4 in the control class. Furthermore, the learning mastery rate in the experimental class was 91%, whereas the control class achieved a mastery rate of 48%. Student responses or interest in learning English using this game-based medium were categorized as positive, indicating that 11th-grade students at MAN 2 Mojokerto showed enthusiasm for learning English. In conclusion, using web-based game media can effectively enhance the quality of student learning outcomes.